2022
DOI: 10.3390/app122010406
|View full text |Cite
|
Sign up to set email alerts
|

The Prevention and Treatment of Medical Diseases in Vulnerable Populations

Abstract: Vulnerability, as a phenomenon of analysis, has long been the subject of extensive social and economic policy reflections, aimed at planning social welfare interventions to support the areas most exposed to the effects of the economic crisis, especially with reference to the presence of potentially weaker segments of the population. [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In the present study, it is important to consider the high DMFT score (5.4), likely due to a "westernization" of the diet favouring caries. Furthermore, worrying is the fact that the percentage of missing teeth (M) or still decayed (D) is higher than the treated teeth (F), confirming the need for a campaign to prevent and treat carious pathology in this category of vulnerable people [31][32][33]. Moreover, this score contrasts with the values observed in the epidemiological study of Vano et al [34], in which the authors reported in a cohort of adult Italian patients an approximate DMFT score of 4.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it is important to consider the high DMFT score (5.4), likely due to a "westernization" of the diet favouring caries. Furthermore, worrying is the fact that the percentage of missing teeth (M) or still decayed (D) is higher than the treated teeth (F), confirming the need for a campaign to prevent and treat carious pathology in this category of vulnerable people [31][32][33]. Moreover, this score contrasts with the values observed in the epidemiological study of Vano et al [34], in which the authors reported in a cohort of adult Italian patients an approximate DMFT score of 4.…”
Section: Discussionmentioning
confidence: 99%
“…Sci. 2023, 13, 3618 2 of 9 The burden tends to be greater in low-and middle-income settings among older people, in women, and in rural and disadvantaged communities due to fewer opportunities to access the most essential eye care services [6,7]. Due to its central position in the Mediterranean Sea, Italy represents an interesting country to explore this issue as it constantly receives migrants coming from different countries [8].…”
Section: Introductionmentioning
confidence: 99%